Coronary Risk Factors in Female Patients With CAD - Adhikary, Prabin (Nepalese Heart Journal, 2008)
This study was conducted to study the association of risk factors for coronary heart diseases in female population. Subjects were included from patients attending three major hospitals within Kathmandu. Patient characteristics were noted and statistical association were sought.